ASSESSMENT OF FEMALE SEXUAL FUNCTION AND QUALITY OF LIFE AMONG BREAST CANCER SURVIVORS WHO UNDERWENT HORMONE THERAPY - Pegorare, Ana Beatriz Gomes de Souza; Silveira, Keslyn da Rosa; No, Ana Paula Simões; Barbosa, Susi Rosa Miziara (Mastology, 2017)
Objective: The aim of this study was to investigate the sexual function and quality of life of breast cancer survival women. Methods: This is a cross-sectional study including 36 women who underwent breast cancer surgery (17 mastectomies and 19 quadrantectomies), sexually active, undergoing hormone therapy, aged 37 to 60 years old. Data were collected through the Female Sexual Function Index (FSFI) and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). Results: In this study, 61.1% of the women had sexual dysfunction. Regarding quality of life, younger women were more impacted in their functional capacity (p=0,049). Conclusion: The prevalence of sexual dysfunction is higher in breast cancer survival women, with hypoactive desire and dyspareunia. Regarding quality of life, greater impairment of functional capacity was observed in young women.